Exploring English Varieties Used by Indonesian Employees: A Linguistic Perspective - Waode Hanafiah; Nining Syafitri; Sanaria Maneba; Baharudin Adu (Hasanuddin University, 2025)
This research explores the common linguistic features found in the spoken English of Indonesian employees in corporate settings, focusing on grammatical, pronunciation, and vocabulary aspects. The primary objective of this research is to identify and analyze the errors made by Indonesian employees when using English in professional contexts. The research utilizes qualitative methods, involving interviews with employees from various corporate sectors, analyzing their spoken English for common linguistic patterns. The research finds that significant grammatical errors include the omission of plural noun markers (-s/-es), incorrect usage of auxiliary verbs, and the overuse of